2013
DOI: 10.1097/aln.0b013e31829bd883
|View full text |Cite
|
Sign up to set email alerts
|

The Anesthesia in Abdominal Aortic Surgery (ABSENT) Study

Abstract: In elective abdominal aortic surgery sevoflurane-based anesthesia did not reduce myocardial injury, evaluated by TnT release, compared with total intravenous anesthesia. These data indicate that potential cardioprotective effects of volatile anesthetics found in cardiac surgery are less obvious in major vascular surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…Long duration (more than 4 h) of sevoflurane inhalation did not provide clinically detectable myocardial protection in elderly patients with CHD in this study. These results are similar to the previous studies [ 15 , 16 ]. RCT which included 385 cases in Switzerland found that, propofol and sevoflurane had no difference in postoperative delirium, myocardial ischemia, and major adverse cardiac events during 1 year follow-up [ 15 ].…”
Section: Discussionsupporting
confidence: 93%
“…Long duration (more than 4 h) of sevoflurane inhalation did not provide clinically detectable myocardial protection in elderly patients with CHD in this study. These results are similar to the previous studies [ 15 , 16 ]. RCT which included 385 cases in Switzerland found that, propofol and sevoflurane had no difference in postoperative delirium, myocardial ischemia, and major adverse cardiac events during 1 year follow-up [ 15 ].…”
Section: Discussionsupporting
confidence: 93%
“…In the most recent randomized study, enrolling 200 patients, Landoni et al did not find a difference between patients anesthetized with sevoflurane or propofol in postoperative cardiac troponin release, 1-year all-cause mortality, rehospitalizations, and adverse cardiac events [ 90 ]. In major vascular surgery, Lurati-Buse et al, Lindholm et al, and Zangrillo et al all failed to show beneficial effects of a sevoflurane-based anesthesia regimen compared with TIVA [ 91 93 ].…”
Section: Emerging Topics In Inhalation Anesthesiamentioning
confidence: 99%
“…However, considering the accumulating evidence indicating the lack of significant benefits of choosing volatile anesthetics over propofol during noncardiac surgery [16,21,[37][38][39], the 2014 ACC/AHA guidelines thus revised the recommendations regarding the choice of anesthetics for noncardiac surgery [26]. Subsequent randomized trials comparing TIVA with sevoflurane also reported no difference in their primary outcomes related to myocardial injury [22,40].…”
Section: Discussionmentioning
confidence: 99%
“…Since cardiovascular complication after surgery involves sympathetic activation, hypercoagulability, arterial thrombosis, and inflammation [17][18][19], the choice of anesthetics has potential to affect the incidence of MACCE after noncardiac surgery in patients with a history of coronary stent insertion. Previous animal studies have demonstrated that volatile anesthetics could reduce the size of myocardial infarction [11,12]; however, clinical studies have reported conflicting results about their effects in patients undergoing noncardiac surgery [20][21][22]. A recent large international randomized trial revealed that volatile anesthetics in cardiac surgical patients did not provide significant cardioprotection compared with total intravenous anesthesia (TIVA) [23].…”
Section: Introductionmentioning
confidence: 99%